UPAYA MENINGKATKAN HASIL BELAJAR KOGNITIF MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM SOLVING KELAS III SD - Intan Kurnia Sari; Khamdun; Diana Ermawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The learning process still focuses on the teacher as the main source of information. This is evidenced by the learning results obtained, there are 4 students who have been completed with a percentage of 34% and 8 students have not completed with a percentage of 66%. The problem in this study is how to improve the learning outcomes of grade III students of SD 1 Tanjungrejo by using the Problem Solving learning model. The purpose of this study was to determine the improvement of learning outcomes of grade III students of SD 1 Tanjungrejo using the Problem Solving learning model.This Classroom Action Research will be carried out in grade III SD 1 Tanjungrejo with research subjects of 12 students and teachers which lasts for 2 cycles each cycle of 2 meetings, the dependent variables in this study are learning outcomes while the independent variables are the use of the Problem Solving learning model. Data collection techniques include interviews, observations, tests, and documentation. The data analysis used is qualitative and quantitative analysis..Based on the results of research that has been carried out by researchers, it can be concluded that through the application of the Problem Solving learning model it can improve the mathematics learning outcomes of class III students at SD 1 Tanjungrejo. With the collaboration of teachers and students in utilizing learning styles with the support of facilities from schools to support the learning process so that it is more optimal.